The reappraisal of Batson’s theory by isolated para-vertebral metastasis of hepatocellular carcinoma - Liang,Po-Chin; Huang,Kai-Wen (PeerJ PrePrints, 2014)
The extra-hepatic metastasis of hepatocellular carcinoma (HCC) usually hints late disease stage and poor prognosis. However, we treated 5 unusual HCC patients with isolated para-vertebral metastasis by tumor excision and the surgical result is satisfactory during 3.5 years follow-up in mean. To explain why the unusual situation of isolated metastasis of HCC occurred, an alternative spreading route of cancer cells bypass pulmonary circulation and avoid pulmonary vascular filtration, the Batson’s plexus, was highly suspected. We supposed that isolated para-vetebral metastases seems not to mean a late disease stage, aggressive management made longer survival possible, and it was confirmed by our clinical experience.
Keywords: Hepatocellular carcinoma; metastasis